APPLICATION OF TEAM GAMES TOURNAMENTS TO INTEREST IN LEARNING MIDDLE SCHOOL STUDENTS - Nur Mala Hayati (JURNAL EDUSCIENCE, 2024)
In the era of globalization, juvenile delinquency is increasing. One reason is the low awareness of religion. Teachers as educators can suppress juvenile delinquency by increasing students' interest to learn PAI (Islamic Religious Education). In school learning activities, educators can choose a variety of methods, one of which is the TGT (Team Games Tournament). This study aims to determine a significant increase between students' learning interest that is applied and that is not applied to the TGT learning model for class IX SMPN 2 Cipanas. This research method is a quasi-experimental design and pre-test and post-test groups. Data collection techniques using questionnaires and documentation. The results of the data show t_count = 3.824 and t_table = 2.042 with a significance of 0.000 <0.005 which is the result of the t-test. the conclusion of the results of the hypothesis test is accepted "There is an effect of implementing team games tournaments on student learning interest in PAI class IX at SMP Negeri 2 CipanasKeywords: team games tournament; interest to learn; Islamic educationAbstrakKenakalan remaja (siswa) yang semakin meningkat adalah salah satu penyebab rendahnya kesadaran beragama. Guru sebagai pendidik dapat menekan kenakalan remaja dengan menumbuhkan minat belajar PAI (Pendidikan Agama Islam) siswa. Kegiatan pembelajaran di lingkungan sekolah, pendidik dapat memilih metode bervariasi salah satunya adalah TGT (Team Games Tournament). Penelitian ini bertujuan mengetahui peningkatan yang signifikan antara minat belajar siswa yang diterapkan dan tidak diterapkan model pembelajaran TGT kelas IX SMPN 2 Cipanas. Metode penelitian ini merupakan quasi eksperimental dan desain rancangan kelompok pra dan pasca uji. Teknik pengumpulan data menggunakan angket dan dokumentasi. Hasil data menunjukan = 3,824 dan = 2,042 dengan signifikansi 0,000 < 0,005 merupakan hasil uji-t. kesimpulan hasil uji hipotesis diterima “Terdapat pengaruh penerapan team games tournament terhadap minat belajar siswa pada mata pelajaran PAI kelas IX SMP Negeri 2 Cipanas Kata Kunci: team games tournament; minat belajar; pendidikan agama Islam